Determination of 60 Food-Borne Stimulant Drug Residues in Animal-Derived Foods by Solid-Phase Extraction Purification and Ultra-High-Performance Liquid Chromatography-Quadrupole/Orbitrap High-Resolution Mass Spectrometry - Liangna He; Qiang Li; Junmei Ma; Meirong Cao; Lixin Fan; Xiaowei Ren; Guohua Shi; Yan Zhang (Journal of Food Quality)
A method for the rapid screening and confirmation of 60 food-borne stimulants in animal-derived foods was developed using the ultra-high-performance liquid chromatography-quadrupole/orbitrap high-resolution mass spectrometry (UPLC-Q/Orbitrap HRMS). After enzymatic hydrolysis at 37°C for 16 h, the samples were extracted with acetonitrile solution. The extraction solution was purified by PRiME HLB pass-through solid-phase extraction cartridge and redissolved by nitrogen blowing. The target compounds of reconstitution fluid were separated by Hypersil GOLD™ VANQUISH column (2.1 mm × 100 mm, 1.9 μm). The raw data were collected for the target compounds in Full Scan-ddMS2 mode, and then the Quan Browser module under Xcalibur software can be used to analyze the quantitative results of the samples. The combination of Tracefinder and mzVault software can realize the qualitative screening and confirmation of the samples. The results showed that the relative deviation of the exact mass of the 60 food-borne stimulants was less than 5.0 × 10−6, which had a good linear relationship in the corresponding concentration, and the correlation coefficient (R2) was greater than 0.9966. The detection limit ranged from 0.05 to 0.5 μg/kg. The quantification limit ranged from 0.1 to 1 μg/kg. The method recoveries ranged from 70.2% to 111.9% with relative standard deviations of 0.05% to 9.00% (n = 6). The method is easy to operate, covers a wide range of targets, and has high efficiency and accuracy. It is suitable for rapid screening and confirmation of various food-derived stimulants in animal-derived foods and provides assistance for food safety in the major events.